Amores de Abat-jour: A cena teatral brasileira e a escrita de mulheres nos anos vinte - Costa Bezerra, Kátia da (Latin American Theatre Review, 2001)
Recently many researchers are interested in rescuing works and names excluded from the Brazilian literary canon. Among these "forgotten" names are several women playwrights, among them Maria Eugênia Celso. During her lifetime, she published three plays. This essay focuses on Amores de Abat-jour, her first play, which was presented in the Teatro Municipal of São Paulo in 1925. The purpose is, first, to provide a historical framework to understand her position in the literary field and to discuss why women’s plays are absent from the canon. Finally, I want to verify how her play dialogues with other discourses circulating during this period. (KCB, in Portuguese)